Cover Picture: Self‐Propelled Janus Mesoporous Silica Nanomotors with Sub‐100 nm Diameters for Drug Encapsulation and Delivery (ChemPhysChem 11/2014). Issue 11 (4th August 2014) - Xuan, Mingjun; Shao, Jingxin; Lin, Xiankun; Dai, Luru; He, Qiang
<x xml:space="preserve">Abstract</x> The cover picture shows that self‐propelled Janus mesoporous silica nanoparticle (MSN) nanomotors with sub‐100‐nanometer sizes, synthesized with a simple metal deposition method, can serve as both autonomous motor and smart cargo, which is favorable to perform drug loading, targeted transportation and release in the vicinity of cells in an organism, as described on p. 2255 by L. Dai, Q. He et al.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>